Expression of the stem cell markers NANOG and SOX2 in the cervical squamous carcinogenesis - Koren, Miha (Radiology and oncology (Ljubljana), 2025)
Background: The aim of the present study was to assess a diagnostic potential of stem cell markers NANOG and SOX2 for classifying cervical squamous intraepithelial lesions (SILs)/cervical intraepithelial neoplasia (CIN). Patients and methods: NANOG and SOX2 expression was evaluated immunohistochemically on 40 patients: in 10 cases each of low-grade SIL (LSIL), high-grade SIL/CIN, grade 2 (HSIL/CIN 2), HSIL/CIN, grade 3 (HSIL/CIN 3), cervical squamous cell carcinoma (CSCC) and their adjacent non-dysplastic squamous epithelium. In addition, human papillomavirus (HPV) genotyping and immunohistochemical staining with p16 and Ki-67 were done. NANOG and SOX2 expression was compared between squamous lesions and controls and between squamous lesions by multiplying staining intensity (SI) by the percentage of positive cells (P) and by multiplying SI by the thickness of staining in epithelium (T) to calculate SI x P and SI x T score. Results: NANOG and SOX2 expression gradually increased from non-dysplastic squamous epithelium via LSIL and HSIL to CSCC. Expression of NANOG and SOX2 was higher in LSIL compared to controls (P < 0.05 for NANOG Si x P and Si x T scores and SOX2 SI x T score) and lower compared to HSIL (P < 0.05 for all SI x P and SI x T scores). HSIL/CIN 3 showed higher SOX2 expression than HSIL/CIN 2 (P < 0.05 for SI x P and SI x T scores). Conclusions: Contrary to p16, NANOG and SOX2 could be effective for distinguishing LSIL from non-dysplastic changes. NANOG and SOX2 could be surrogate markers for differentiating LSIL from HSIL. Moreover, SOX2 could be helpful for distinguishing HSIL/CIN 2 from HSIL/CIN 3. Further studies with larger numbers of patients and molecular insights are needed.
Keywords: cancer stem cell; cervical cancer; cervical intraepithelial neoplasia; intraepitelijska neoplazija materničnega vratu; matične celice raka; NANOG; rak materničnega vratu; skvamozan intraepitelijska lezija; SOX2; squamous intraepithelial lesion